COVID-19 KNOWLEDGE, ATTITUDE, AND PRACTICES BETWEEN PAKISTANI MEDICAL AND NON-MEDICAL STUDENTS - Bushra Suhail; Ayesha Masood; Javaria Baig; Sara Mukhtar; Sarah Aftab; Tahir Jamil (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: This study investigated medical and non-medical students’ knowledge, attitude, and preparedness regarding COVID-19 pandemic, to groom volunteers and future healthcare providers in a better way.METHODOLOGY: This cross-sectional study was completed from April to May 2020 during the first wave of COVID-19. An online questionnaire was distributed using internet and social media (SM). The questionnaire was composed of several parts concerning to demographic data, knowledge, attitude, and practices.RESULTS: This study included 1851 students [1041(56.54% medical, 810(43.46%) non-medical students)]. Medical students had significantly better knowledge about the contagious nature, spread and treatment of coronavirus. Non-medical students showed more risky behavior compared to medical students (p = 0.005). The use of masks and the frequency of handwashing was better among medical students as compared to non-medical students (p< 0.001; p< 0.014, respectively). The odds ratio indicates that students of the age group 21-25 years (45%) and medical students (75%) were more likely to have a positive attitude.CONCLUSION: This study revealed good knowledge, positive attitudes, and good practices towards COVID-19 among medical students. Still, a minority of participants from both groups revealed misconceptions and relatively poor conceptual knowledge regarding the disease.